Design of Steel Plate Grasping Vacuum Equipment on TruLaser 3030 with Servo Motor - Wijaya, Ambrosius Vitoaji Kepra; Sebayang, Melya Dyanasari (Talenta Publisher, 2022)
AÂ vacuum gripperÂ is a device that uses a vacuum cup as a suction device and holds the workpiece load so that the workpiece can go through the process of moving from one position to another. In this research, the gripping vacuum is the main tool in the sheet metal material transfer machine so that the material can be easily moved from the wooden pallet to the TruLaser 3030 fiber machine table. The process of making this machine design requires careful calculation of the formula so that the appropriate machine components are obtained to lift material loads. The components needed in the design of this machine include a gripper vacuum, servo motor, load-bearing shaft, transmission drive, gear transmission, and a steel frame using a 300 x 300 Wide Flange Beam as a support for the whole machine. The sheet metal material used as the load is SS400 material sheet metal with a thickness of 15 mm and an area dimension of 2.44 m x 1.22 m. For this reason, strong components are needed and can withstand vertical and horizontal loads from the movement of materials and the load of the sheet metal material itself. It is recommended to use a suction motor on a gripping vacuum with a suction power of 48 m3/hour and electric power of 1.3 kW. In addition, the servo motor used must be able to withstand a load of 350 kg with a design power of 171.7 watts and a torque of 93 Nm, and straight gears with a ratio of 4:3.